Clinically determined and self‐reported dental status during and after pregnancy among low‐income Hispanic women. (25th July 2013) - Weintraub, Jane A.; Finlayson, Tracy L.; Gansky, Stuart A.; Santo, William; Ramos‐Gomez, Francisco
Abstract Objectives This analysis assessed, during and 1 year after pregnancy: a) the prevalence of and relationship between self‐reported and clinically determined dental caries and oral health status, and whether self‐reports are a potential proxy for professional determination; and b) factors associated with high levels of professionally determined or self‐reported oral disease. Methods Data are from a randomized clinical trial of 301 pregnant, low‐income Hispanic women at the California–Mexico border to compare two interventions to prevent early childhood caries. Interviews and dental examinations were conducted at enrollment (second trimester) and 1‐year postpartum (PP). Results During pregnancy and PP, 93 percent had untreated caries and most had gingival inflammation. Sensitivity and specificity of self‐reported measures compared to dentists' determinations were modest (ranging from 45‐80 percent for sensitivity and 41‐77 percent for specificity at both time points); positive predictive values for women reporting current tooth decay or fair/poor oral health were high (>94 percent), but negative predictive values were low (<23 percent). In a bivariate GEE model, factors associated with fair/poor self‐reported oral health during and after pregnancy included self‐reported dental symptoms (current tooth decay, bleeding gums without brushing), dental behaviors (not flossing) and number of decayed tooth surfaces. In a logistic regression model, the only significant factor PP associated with less extensive untreated disease was if women ever had their teeth cleaned professionally (OR = 0.44). Conclusions There is a great need for dental treatment in this underserved population both during pregnancy and PP. Women may not be able to accurately recognize or act on their treatment needs. At baseline and PP, few demographic or behavioral factors were associated with either self‐reported or clinically determined oral disease (e.g., being less educated or acculturated and not flossing) in the bivariate analyses. Ever having a professional teeth cleaning significantly predicted less disease PP.